TANGGUNG JAWAB DIREKSI TERHADAP PEMEGANG SAHAM BERITIKAD BAIK ATAS PEMBELIAN KEMBALI SAHAM YANG BATAL KARENA HUKUM - MARHARA TUA MULYADI TAMBUNAN; RAMLI SIREGAR; WINDHA WINDHA (TRANSPARENCY, 2013)
The  responsibility of director as the result of negligence in performing the work to the stakeholders is as full  responsibility. Regarding the responsibility,  the director must return all losses suffered by stakeholders since repurchase  of the shares is against  the prevailed law in company. The thesis  studied  some  problems about the responsibility  of  director and stakeholders in running  company, how is legal clause governing  repurchase of share by the company, and how is the responsibility of director to  stakeholders  with  good-will  on  repurchase of postponed shares by legal  according to  Act No 40  of  2007 concerning with  limited company. The method of research used  was  normative  research method  by collecting  data from library and secondary data from books, articles, newspapers and magazines  as well as  laws. The results of research concluded that the responsibility of director is  fully to implement and run  the company, whereas the responsibility of stakeholder is limited to  and  focus on  the  principle of  separate  entity and corporate entity producing limited stakeholders. Legal clause governing  repurchase of  shares  by the company   is  UUPT which allows the company  to  repurchase its shares and can be seen in  article  37, article  38, article  39 and article  40  UUPT. Kata Kunci: Tanggung Jawab Direksi, Pemegang Saham Beritikad Baik, Pembelian Kembali Saham.